ANALISIS KETERAMPILAN MENGAJAR GURU PNS, P3K, DAN HONORER DAERAH TERHADAP PEMBELAJARAN SAINS DI SEKOLAH DASAR - Muhammad Ishak; Nurmalina Nurmalina; Musnar Indra Daulay (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Teacher teaching skills are one of the pedagogical skills that must be mastered by primary school teachers, whether they are civil servants, government employees with work agreements, or regional honorary. This research aims to quantitatively describe the teaching skills of teachers who are civil servants, government employees with work agreements, and regional honorary teachers towards science learning in primary schools. The method used in this research is quantitative descriptive method. This method has six stages, namely: formulating the problem, determining the theoretical basis, formulating hypotheses, collecting data, analysing data, and drawing conclusions. The research sample totalled eight teachers, consisting of two teachers with civil servant status, three teachers with government employee status with work agreements, and two teachers with regional honorary status. The data collection technique used was observation of teachers' skills assessment when teaching science in the classroom. The results showed that the teaching skills of civil servant teachers, government employees with work agreements, and regional honorary teachers for science learning in elementary schools did not have significant differences. All three have almost the same average value of teaching skills. All three are in the good category. Civil servant teachers should continue to be mentored so that they can improve their teaching skills more than teachers who are still government employees with work agreements, while both teachers who are still government employees with work agreements and regional honorary are expected to become civil servants so that they continue to be motivated and the distribution of teachers in primary schools that are still lacking can be handled. Future researchers are expected to research other teacher skills so that teacher skills become complete and comprehensive.